Structural, biochemical, and physiological characterization of photosynthesis in leaf-derived cup-shaped galls on Litsea acuminata - Huang, Meng-Yuan (BMC Plant Biol, 2015)
BACKGROUND: The source and sink relationships between insect-induced galls and host plant leaves are interesting. In this research, we collected cup-like galls induced by Bruggmanniella sp. (Diptera: Cecidomyiidae) on host leaves of Litsea acuminata and assessed them to investigate source-sink relationships between galls and host leaves. We characterized several of their photosynthetic characteristics including chlorophyll fluorescence (Fv/Fm), stomatal conductance, and photosynthetic capacity, biochemical components such as total soluble sugar, starches, free amino acids, and soluble proteins. The structural analyses were performed under confocal, light, and scanning electron microscopies. RESULTS: Compared with host leaves, galls exhibited slightly lower chlorophyll fluorescence; however, stomatal conductance and photosynthetic capacity were not detected at all. Galls accumulated higher total soluble sugars and free amino acids but less soluble proteins than host leaves. No stomata was observed on exterior or interior gall surfaces under light or scanning electron microscopy, but their inner surfaces were covered with fungal hyphae. Confocal imagery showed a gradient of chloroplasts distribution between gall outer and inner surfaces. CONCLUSIONS: Our results strongly suggest that leaf-derived cecidomyiid galls are a type of chlorophyll-deficient non-leaf green tissue and consists on a novel sink in L. acuminate.